Peran Komunikasi Interpersonal Staf Front Office Dalam Meningkatkan Pelayanan Publik di Kecamatan Bekasi Utara - Simbolon, Alicia Amanda; Rahastine, , Mareta Puri (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Public service is a crucial element in realizing good governance that is responsive to the needs of society. In this context, interpersonal communication plays a strategic role, especially for front office staff who serve as the frontline in direct interactions with the public. This study aims to explore and understand the role of interpersonal communication among front office staff in improving public service delivery in North Bekasi District. This research employs a descriptive qualitative approach to gain an in-depth understanding of the interpersonal communication processes within public service. The study was conducted at the North Bekasi District Office, located at Jalan Raya Perjuangan No.1, Harapan Baru Subdistrict, Bekasi City, West Java. The unit of analysis consists of individuals, specifically front office staff and service users. Informants were selected purposively, based on criteria relevant to the research objectives. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using the interactive model of Miles and Huberman. The results indicate that effective interpersonal communication plays a central role in shaping the quality of public services. Front office staff who are able to communicate effectively—both verbally and nonverbally—significantly influence public satisfaction. Key factors contributing to positive service experiences include friendliness, the ability to adapt communication styles to different public characteristics, and the skill to handle communication challenges, such as dealing with emotional or special-needs service users. The study concludes that strengthening the interpersonal communication skills of front office staff through continuous training is essential to improving overall public service quality. Effective communication not only facilitates service processes but also fosters trust between the government and the public in North Bekasi District.